2023
DOI: 10.1080/21655979.2023.2252138
|View full text |Cite
|
Sign up to set email alerts
|

Spent substrate from mushroom cultivation: exploitation potential toward various applications and value-added products

Carlos Martín,
Georgios I. Zervakis,
Shaojun Xiong
et al.

Abstract: Spent mushroom substrate (SMS) is the residual biomass generated after harvesting the fruitbodies of edible/medicinal fungi. Disposal of SMS, the main by-product of the mushroom cultivation process, often leads to serious environmental problems and is financially demanding. Efficient recycling and valorization of SMS are crucial for the sustainable development of the mushroom industry in the frame of the circular economy principles. The physical properties and chemical composition of SMS are a solid fundament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 200 publications
0
6
0
Order By: Relevance
“…They also have minimal effect on non-target populations. They frequently have a shorter shelf-life and low-medium efficacy [5,48]. On a large scale, microbial-based inoculants, such as Trichoderma spp., are successfully used as biocontrol agents (BCAs) for the pathogen control of fungi such as Chondrostereum purpureum, Fusarium oxysporum, Rhizoctonia solani, and many other soil-borne microbes [49,50].…”
Section: Utilization Of Smc To Control Crop Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have minimal effect on non-target populations. They frequently have a shorter shelf-life and low-medium efficacy [5,48]. On a large scale, microbial-based inoculants, such as Trichoderma spp., are successfully used as biocontrol agents (BCAs) for the pathogen control of fungi such as Chondrostereum purpureum, Fusarium oxysporum, Rhizoctonia solani, and many other soil-borne microbes [49,50].…”
Section: Utilization Of Smc To Control Crop Diseasesmentioning
confidence: 99%
“…In addition, drying fresh SMC is an extremely energy-intensive and impractical process. Furthermore, the handling and disposal of SMC poses a major environmental risk because it releases greenhouse gasses into the atmosphere through natural anaerobic digestion (which often occurs in the piles created during temporary storage), foul odors, and leachate drainage that contaminates and eutrophicates water receptors depleting dissolved oxygen [5]. The amount of SMC produced in the mushroom industry requires effective management [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, detailed research is necessary, including screening of microorganism systems that will effectively dissolve waste materials in natural systems, including variations in the method of introducing microorganisms. Nitrogen, Phosphorous, and Humic acid [22] For instance, research on keratinases and the in vitro degradation of feathers revealed that keratin cannot be broken down by a single keratinase enzyme. The activity of keratinases is insufficient to break disulfide bonds.…”
Section: Bio-waste Materials As Source Of Nutrientsmentioning
confidence: 99%
“…These results highlight the enriched micro-and macro nutritional content in SMC and SOS compared with peat, emphasizing their potential utility from a plant nutrition perspective. Previous studies (Martín et al, 2023) have alluded to the promise of SMC in this context, attributing the nutrient enhancement to the supplementation that occurs during pre-mushroom cultivation stages (Carrasco et al, 2018). However, the amount of copper in SOS is of concern if it occurs in higher concentrations, as highlighted by Góngora-Gómez et al (2017).…”
Section: Nutrient Contentmentioning
confidence: 99%